TERRORISMIN THE AGE OFCONTEMPORARYCONFLICTS (Research Bulletins of the Faculty of Economic Sciences, 2021)
At the beginning ofthe twenty-firstcenturythe following concepts became widespread: globalism, terrorism, asymmetricmodern world, theproblemsof poverty, hunger andincome inequalityin society.All these risks can lead to terrorist activity. The author of this article believes that proper prevention of terrorism begins with understanding and analysis of the socio-political reasons and not just the symptoms. The article attempts to answer the questions: Is asymmetry of the modern world the phenomenon of the unit or everyday? Is the asymmetry of the modern world the problem just inside one country or beyond its borders? The first part of the paper describes the concept of contemporary asymmetric conflicts. The second describes the problems of the characteristics of asymmetric terrorism conflicts, while the third part describes selected threats in the early twenty century. The accepted method of research is a critical analysis of documents and literature. The author hopes that it will launch alarger discussion on the asymmetric threats of the modern world.